Use of EN Snare device for successful repositioning of the newest self-expanding transcatheter heart valve. (December 2018) - Beute, Tyler J; Nolan, Mark A; Merhi, William M; Leung Wai Sang, Stephane
Once a self-expanding transcatheter aortic valve replacement is fully deployed, a snare device must be used to retrieve it. Minimal data are available regarding technique, efficacy, and complications associated with the retrieval of such valves. Here, we present two patients in which an EN Snare ® Device (Merit Medical System, South Jordan, UT, USA) was safely and effectively used to retrieve and reposition the latest generation self-expanding transcatheter aortic valve replacement.